Importance of Dexamethasone for Control of Edema and Pain at Surgical Site in the Mandibular Fracture Osteosynthesis Treatment - Sonia Mubeen, Irum Farheen, Saddique Aslam Khattak, Khurram Nadeem, Ikram Manzoor, (Pakistan Journal of Medical & Health Sciences, 2023)
Dexamethasone is highly sensitive to low dosages and is widely used in oral surgical procedures with variable dosage, timing and route of administration. Aim of the study: Comparison of the results of treatment with placebo and dexamethasone in terms of the edema and mean pain at the surgical site in patients with osteosynthesis of the mandible. Methods: This randomised controlled trial was held in the Oral and Maxillofacial surgery department of different dental hospitals of Lahore for one-year duration from June 2021 to May 2022. A total of 100 patients with mandibular fractures of both sexes, aged 20 to 60, were included in the study. Patients with other associated facial fractures, patients with a history of diabetes mellitus, heart and kidney disease due to chronic drug use, and pregnant women were excluded. The experimental group was given eight milligrams of dexamethasone with submucosal infiltration at the surgical incision site and the normal saline was given in the control group. Edema and pain were evaluated by means of visual analog scale at a nine-line measurement at twenty-four and seventy-two hours postoperatively, respectively. Results: In this study, 24 hours after the procedure, the visual analog scale was 2.16 ± 0.89 in group I (experimental group) and 3.51 ± 1.23 in group II (placebo group) and 2.29 ± 0.89 in control group and 0.62 ± 0.19 in group given dexamethasone at seventy-two hours. Postoperative edema score was significantly less up to 4.26 ± 1.42 in patients receiving group I (dexamethasone), in comparison to group II (placebo group) 5.38 ± 1.01 twenty-four hours afterwards surgical procedure and 2.06 ± 0.64 in the placebo group and 0.042 ± 1.23 in the group given dexamethasone at seventy-two hours. Conclusions: This study found that patients with osteosynthesis of the mandible had lower rates of pain and swelling after applying dexamethasone to the surgical site. Keywords: Dexamethasone, Mandibular osteosynthesis, Edema.